Wet Spring Rolls Innovation with Banana Kepok Peel - Din Dinar Safira Kamal; Budi Hermawan; Hary Hermawan (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
Kepok banana (Musa Paradisiaca Linn) is a type of fruit plant that can be harvested from all tree parts. Researchers reinvented wet spring rolls in this experiment by substituting kepok banana peels for the main filling, bamboo shoots. This study aims to determine the preference and acceptability of wet spring rolls with kepok banana peel filling compared to bamboo shoots in terms of taste, flavour, colour, and texture. This study employs the descriptive quantitative method, organoleptic testing and the difference test. This study was conducted on the STP AMPTA Yogyakarta campus using a purposive sampling technique with up to 15 panellists. The author used literature studies, questionnaires, and documentation to collect data. According to the results of the organoleptic test, 73.3% of the panellists said they liked the taste. Regarding flavour, 53.3% of the panellists said they liked it. Regarding colour, 60% of the panellists said they liked it. Sixty per cent of the panellists said they liked the texture. The average value of the four aspects in the different tests is more significant than number six. This research suggests that wet spring rolls with kepok banana peels are just as good as wet spring rolls with bamboo shoots. Wet spring rolls with banana peel stuffing have a taste value of 6,53, while bamboo shoots stuffed to have a value of 6,87. Wet spring rolls with banana peel stuffing have an average flavour value of 6,53, while bamboo shoots stuffed have an average flavour value of 6,87. Regarding colour, wet spring rolls with banana peel stuffing have an average value of 6,13, while bamboo shoots stuffed have an average value of 6,53. Wet spring rolls with banana peel stuffing have an average texture value of 6,47, while bamboo shoots stuffed have an average texture value of 6,20.